Prevalence and correlation analysis between post-traumatic stress disorder and analgesic use in survivors of ICU in China - Pan, Yanbin; Yan, Jianlong; Lin, Xiaolan; Luo, Weixiang; Huang, Qiongfang; Lin, Changao; Lu, Wanxian (Journal of the Pakistan Medical Association, 2023)
Objectives: To investigate the prevalence of post-traumatic stress disorder in intensive care unit survivors, and disorder’s correlation with analgesia use. Method: The single-centre retrospective cohort study was conducted at the First Affiliated Hospital of Jinan University, China, and comprised data from February 2021 to January 2022 related to patients of either gender aged 18 years who were admitted to the intensive care unit and were successfully transferred out to the general ward. Post-traumatic stress disorder Checklist-Civilian Version scale was used for follow-up within one month of getting transferred out of intensive care. Data was analysed using Empower Stats. Results: Of the 121 patients with mean age 54.34±18.19 years, 52(43percent) were positive for post-traumatic stress disorder; 32(61.5percent) males and 20(38.5percent) females with mean age 54.48 ± 19.56 years. The remaining 69(57percent) patients were negative; 40(58percent) males and 29(42percent) females with mean age 54.23±17.24 years (p 0.05). The positive rate of re-experiencing symptoms was noted in 68(56.20percent) patients. Analgesia usage was positive in 61(50.4percent) cases and negative in 60(49.6percent) cases. Compared to the non-analgesic group, the risk of post-traumatic stress disorder occurrence in the analgesic group was significantly high (p=0.018). The duration of analgesia usage 24-48h was also significant (p=0.017). Conclusions: There was a high prevalence of post-traumatic stress disorder in intensive care unit survivors, which was affected by the use of analgesics in intensive care settings. Key Words: Post-traumatic stress disorder, PTSD, Analgesics, Intensive care unit.